Collaborative Governance in Road Construction in Molowahu Village, Tibawa District, Gorontalo Regency - Sri Fitriana Isa; Widya Kurniati Mohi; Rifka S. Akibu; Sakbir (Universitas Muhammadiyah Palu, 2026)
Road infrastructure development constituted an important factor in improving community welfare because it affected mobility and socio-economic activities. To support the effectiveness of such development, collaboration among stakeholders through the application of Collaborative Governance principles wa's required. This study aimed to analyze the application of Collaborative Governance in the road development in Molowahu Village. Tibawa District, Gorontalo Regency. The research employed a qualitative descriptive approach with a case study design, data were collected through observation, interviews, and documentation. The findings indicated that all Collaborative Govemnance indicators had been applied, including initial conditions, institutional design, facilitative leadership, collaborative processes characterízed by face to face dialogue, trust-building, commitment to the process, shared understanding, and interim outcomes. However, none of these indicators had been implemented optimally. Constraints in authority and limited budgets were identified as the primary causes that prevented the realization of physical road construction, so collaborative results remained limited to non physical aspects and had not yet been able to drive physical development. Therefore, strengthening collaboration was necessary to accelerate road development more effectively and concretely.